Impressive of Periodic and Insecticides on Leucinodes orbonalis Infestation on Solanum melongena - Kumar, Kamalesh (Journal for Research in Applied Sciences and Biotechnology, 2023)
Six insecticides, namely Cypermethrin, Dimethoate, Carbaryl, Diflubenzuron, Neem and Bacillus thuringiensis (dipel) were tried against brinjal shoot, fruit borer and seed yield. Among them Cypermethrin, and Dimethoate were found to be the most effective in reducing the damage of shoot, fruits, and seed yield and thereby increasing the yield of brinjal fruits. In the present investigation, the shoot damage due to B.t. + diflubenzuron, B.t. + carbaryl was 8.52 and 6.84 percent in 2021- 22 and 9.93 and 9.45 in 2022-23 respectively, while the shoot infestation in control was 12.07 and 13.96 percent respectively, while B.t.alone proved to be very less against the shoot borer. Fruit infestation on both weight and number basis was minimum due to the treatment of B.T. application at transplanting followed by a combined application of B.T. + cypermethrin and B.T. + dimethoate. It might be due to that chemical pesticidal act as stressors and are frequently synergistic when combined with microorganisms such as Bacillus thuringienses.